Keefektifan Kurikulum Merdeka Terhadap Hasil Belajar Siswa Sekolah Dasar Fase B Melalui Problem Based Learning (PBL): Studi Literatur - Prameswari, Malika; Pratiwi, Oktavani Putri; Nabila, Wardah Nada (Lembaga Intelektual Muda (LIM) Maluku, 2024)
There are several things that must be prepared before learning and after learning in an independent curriculum with differentiated learning and assessment. The aim of this research is to find out how effective the implementation of the independent curriculum through PBL is on the learning outcomes of Phase B elementary school students. The method used in this research is a qualitative method with a type of literature study where we conducted research by summarizing several materials sourced from journals, books, and other sources related to knowledge about the curriculum and its implementation in learning in Indonesia on student learning outcomes. From the application of the Problem Based Learning learning model, it can be seen that the learning outcomes of students have increased because the Problem Based Learning model is a problem-based learning model that is directed at students to increase their activity during the learning process and improve students' critical thinking skills which can solve existing problems so that new ideas or thoughts emerge in solving the problem